'Who is this body?' – A qualitative user study on 'The Machine to be Another' as a virtual embodiment system. Issue 1 (1st September 2020) - Harth, Jonathan; Brücher, Maximilian; Kost, Nele; Hartwig, Ann-Danielle; Schäfermeyer, Bernhard; Holkin, Erwin; Gottschalk, Hanna
ABSTRACT: Like no other medium, virtual reality (VR) offers new possibilities to alter the perception of reality. These possibilities are mainly related to the feeling of presence in a virtual environment. With the VR performance 'The Machine to be Another' (TMTBA), we find an innovative embodiment system that enables a virtual body swap between two users. Hence, we conceptualise the performance as some kind of breaching experiment in order to alter self- and body perception. With the use of TMTBA and a qualitative research approach, we hope to gain a closer insight into the formation, alteration and persistence of body images. This challenges the phenomenological idea that our sense of bodily presence is essentially anchored in our physical or 'objective' body as we know it and seems to potentially expand our notion of what bodily presence can mean.